SYMBOLIC MEANINGS IN THE ATTUMATE TRADITION IN THE COMMUNITY OF NORTH GALESONG, TAKALAR DISTRICT - Nurismi Auliyah; Agussalim AJ; Asia M3 (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to describe the icons, indices and symbols contained in the process of implementing attumate in the community in North Galesoong, Takalar Regency in terms of Charles Sanders Peirce's semiotic theory. This type of research is qualitative with a qualitative descriptive research design. The methods used in collecting data for this research were observation, interviews and documentation. The results of this research show that in the process of implementing the attumate tradition in the community in North Galesong, Takalar Regency, it has the meaning of (1) an icon, namely one that resembles the shape of the original object which shows the natural relationship between the signifier and the signified. Data that includes icons in the attumate tradition are taibani and doek; (2) the meaning of an index is a sign that has a phenomenal or existential relationship between the actor and the object or a cause and effect relationship being signified. The data included in the index contained in the attttumate are pakdupang, nibacangi kanrena, nipanngajiangi, nisikkiriki, nilappassi allonna, appassidakka; (3) the meaning of a symbol is a sign that has a relationship with its signifier and also with its signified. The data included in the symbols contained in the attumate are kanre ri kapparak, unti tekne tallullaklak, kanrejawa, katinroang, kadera, songkolok sigang meat ri tokdok, pannganreang, passalingang siagang tope, jakjakkang, taibani, lamari. In general, the meaning contained in the attumate tradition among the people in North Galesong, Takalar Regency is for safety, enjoyment and tranquility for the deceased and the hope that they will be placed next to Allah, namely in heaven.